Financial liberalisation in Zimbabwe : what went wrong? - Maravanyika, Edward (University of Cape Town, 2016)
Bibliography: pages 84-86. === Zimbabwe officially abandoned financial repression when it introduced financial liberalisation in 1991. Since independence in 1980, the government had used interest rate controls and strict foreign exchange regulations in order to control the economy. This mini-dissertation will analyse financial reforms in Zimbabwe from 1991 to 1997. The analysis will consider whether there were statistical grounds to believe that the financial liberalisation hypothesis would work. That is, do real interest rates in Zimbabwe have a statistically significant and positive relationship with real money demand and real savings? This paper will show that in Zimbabwe this relationship does indeed exist. The existence of such a relationship suggests that the freeing of interest rates in 1991 should have raised savings and financial intermediation as the theory predicts. However, as this did not happen, this paper will put forward reasons why, from 1991 to 1997, lifting controls in the economy did not increase savings as expected.